Features of using of specialized information systems (IS) in the management processes of domestic enterprises - Гречаник, Б. В.; Лагдан, В. А. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Defined key selection criteria of specialized information systems for use in the management of the Ukrainian enterprises (in the socio-economic systems mìcrolevel). Outlines the most optimal for their species by the criterion of adaptivity to the domestic conditions of management. Offered the most promising IP from the perspective of the possibilities of their integration in the control system on enterprices.